Intimate Partner Violence and Attachment Styles as Factors Associated with Coping Stress Styles Among Iranian Women - Sadegh Mohammadi, Fatemeh (Journal of interpersonal violence, 2025)
The current study sought to examine attachment styles as mediators between intimate partner violence (IPV) and stress coping styles among Iranian women. Data were collected from September to December 2020. The study population was composed of 102 women who were referred to Social Emergency Centers in Isfahan and affected by domestic violence. They were given self-report questionnaires to measure IPV (the Haj-Yahia Violence Questionnaire), Stress Coping Styles (CISS), and Attachment Styles (AAQ). Structural Equation Modeling was used to test the hypothesized relationships. Sexual IPV victimization was related to both avoidant attachment (β = .229, p = .015) and anxious attachment (β = .245, p = .008). Anxious attachment style was related to emotion-oriented coping (β = .437, p = .000). There was a negative relationship between avoidant attachment and anxious attachment (β = −.237, p = .032) with avoidance-oriented coping. Sexual IPV victimization and economic IPV victimization were associated with avoidance-oriented coping (β = −.225, t = 0.816, p = .015; β = .188, t = 0.816, p = .044). Women who had experienced IPV and had an insecure attachment style were more likely to utilize avoidance and emotional coping strategies. For women who had a secure attachment style, there was no association was found between IPV victimization and coping styles. Attachment styles may influence the relationship between IPV and coping strategies in Iranian women who have experienced violence.